Institutional regulations, environmental degradation and green GDP in Malaysia - Cheah, Chan Fatt (2019)
Malaysia currently uses the gross domestic product (GDP) as the measurement of national income. However, when measured alone, GDP is limited because it only represents the final monetary value of goods or services. Measuring Green GDP can help to address this shortcoming because it considers the environmental impacts. Malaysia has the aim of becoming a high-income economy, one way this can be achieved is through the growth of green industries and by using Green GDP to promote higher economic growth.